Arabinogalactan-Proteins from Primary and Mature Roots of Radish (Raphanus sativus L.) - Tsumuraya, Yoichi (1988)
Organ-specific variations in blood group H-like activity were observed in developing radish plants. A temporary increase in serological activity was found to occur in the roots at the earlier stages of development. Arabinogalactan-proteins (AGPs) were isolated from primary and mature roots, and investigated for changes in their physicochemical properties, structure, and serological activities. These root AGPs were composed mainly of l-arabinose and d-galactose but were distinguishable from each other in their contents of l-fucose as well as of protein and hydroxyproline. The structures of the carbohydrate moieties of the root AGPs were essentially similar to those of AGPs isolated from seeds and mature leaves in that they consisted of consecutive (1→3)-linked β-d-galactosyl backbone chains having side chains of (1→6)-linked β-d-galactosyl residues, to which α-l-arabinofuranosyl residues were attached in the outer regions. One prominent feature of the primary root AGPs was that they contained appreciable amounts of l-fucose, which was presumably responsible for expression of the serological activity. In their immunological reactions with rabbit anti-radish leaf AGP antibody, the root AGPs were shown to share common antigenic determinant(s) with those of seed and leaf AGPs.